Impact of antiseptics on onestage, full-mouth disinfection - Marc Quirynen (Blackwell Synergy, 2006)
Department of Periodontology, Research group for Microbial adhesion, School of Dentistry, Oral Pathology and Maxillo-Facial Surgery, Faculty of Medicine, Catholic University of Leuven, Leuven, Belgium